Airway Smooth Muscle Dynamics and Hyperresponsiveness: In and outside the Clinic. (17th October 2012) - Noble, Peter B.; Ansell, Thomas K.; James, Alan L.; McFawn, Peter K.; Mitchell, Howard W.
Abstract : The primary functional abnormality in asthma is airway hyperresponsiveness (AHR)—excessive airway narrowing to bronchoconstrictor stimuli. Our understanding of the underlying mechanism(s) producing AHR is incomplete. While structure-function relationships have been evoked to explain AHR (e.g., increased airway smooth muscle (ASM) mass in asthma) more recently there has been a focus on how the dynamic mechanical environment of the lung impacts airway responsiveness in health and disease. The effects of breathing movements such as deep inspiration reveal innate protective mechanisms in healthy individuals that are likely mediated by dynamic ASM stretch but which may be impaired in asthmatic patients and thereby facilitate AHR. This perspective considers the evidence for and against a role of dynamic ASM stretch in limiting the capacity of airways to narrow excessively. We propose that lung function measured after bronchial provocation in the laboratory and changes in lung function perceived by the patient in everyday life may be quite different in their dependence on dynamic ASM stretch.